2020
DOI: 10.1038/s41586-020-2497-0
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar RNA polymerase II drives ribosome biogenesis

Abstract: Proteins are manufactured by ribosomes-macromolecular complexes of protein and RNA molecules that are assembled within major nuclear compartments called nucleoli 1,2. Existing models suggest that RNA polymerases I and III (Pol I and Pol III) are the only enzymes that directly mediate the expression of the ribosomal RNA (rRNA) components of ribosomes. Here we show, however, that RNA polymerase II (Pol II) inside human nucleoli operates near genes encoding rRNAs to drive their expression. Pol II, assisted by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
159
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(193 citation statements)
references
References 39 publications
15
159
4
1
Order By: Relevance
“…342,348 In a recent study, R-loops generated by RNA polymerase II localised to non-coding regions in ribosomal DNA and had positive regulatory effects on ribosomal RNA expression by RNA Pol1 in the nucleoli. 351 Aberrant R-loop formation threatens genomic stability, notably inducing replication and translational stress as they form roadblocks to polymerase processivity that promote DNA breaks and activate both ATM and ATR pathways. However, the relationship between DNA damage and R-loop formation is intricate as R-loops trigger DNA damage and conversely DNA damage favours R-loop formation.…”
Section: Non-b Dna Structuresmentioning
confidence: 99%
“…342,348 In a recent study, R-loops generated by RNA polymerase II localised to non-coding regions in ribosomal DNA and had positive regulatory effects on ribosomal RNA expression by RNA Pol1 in the nucleoli. 351 Aberrant R-loop formation threatens genomic stability, notably inducing replication and translational stress as they form roadblocks to polymerase processivity that promote DNA breaks and activate both ATM and ATR pathways. However, the relationship between DNA damage and R-loop formation is intricate as R-loops trigger DNA damage and conversely DNA damage favours R-loop formation.…”
Section: Non-b Dna Structuresmentioning
confidence: 99%
“…LLPS allows for the enrichment of specific factors while excluding others from the condensates, thereby creating a unique environment that either favours or restricts certain biochemical reactions 5 . LLPS drives the formation of multiple membraneless compartments, including but not limited to P granules, the nucleolus, facultative heterochromatin, transcriptional complexes and DNA repair centres 6 – 14 . These phase-separated compartments are dynamic, and the processes mediating their formation and dissolution are tightly regulated.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a nucleolar localization and function of general transcription factors of RNA polymerase II was reported for TFIIH (Hoogstraten, Nigg et al, 2002, Iben et al, 2002). A seminal publication indicates that nucleolar RNA polymerase II transcription is essential for proper rRNA biogenesis and processing (Abraham, Khosraviani et al, 2020). The authors showed that RNA polymerase II transcribes intergenic spacers (IGSs) of the rDNA to maintain nucleolar organization and hence rRNA synthesis and maturation.…”
Section: Discussionmentioning
confidence: 99%